z*z-(2+1i)z+(-1+7i)=0

Simple and best practice solution for z*z-(2+1i)z+(-1+7i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z*z-(2+1i)z+(-1+7i)=0 equation:


Simplifying
z * z + -1(2 + 1i) * z + (-1 + 7i) = 0

Multiply z * z
z2 + -1(2 + 1i) * z + (-1 + 7i) = 0

Reorder the terms for easier multiplication:
z2 + -1z(2 + 1i) + (-1 + 7i) = 0
z2 + (2 * -1z + 1i * -1z) + (-1 + 7i) = 0

Reorder the terms:
z2 + (-1iz + -2z) + (-1 + 7i) = 0
z2 + (-1iz + -2z) + (-1 + 7i) = 0

Remove parenthesis around (-1 + 7i)
z2 + -1iz + -2z + -1 + 7i = 0

Reorder the terms:
-1 + 7i + -1iz + -2z + z2 = 0

Solving
-1 + 7i + -1iz + -2z + z2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 7i + -1iz + -2z + 1 + z2 = 0 + 1

Reorder the terms:
-1 + 1 + 7i + -1iz + -2z + z2 = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 7i + -1iz + -2z + z2 = 0 + 1
7i + -1iz + -2z + z2 = 0 + 1

Combine like terms: 0 + 1 = 1
7i + -1iz + -2z + z2 = 1

Add '2z' to each side of the equation.
7i + -1iz + -2z + 2z + z2 = 1 + 2z

Combine like terms: -2z + 2z = 0
7i + -1iz + 0 + z2 = 1 + 2z
7i + -1iz + z2 = 1 + 2z

Add '-1z2' to each side of the equation.
7i + -1iz + z2 + -1z2 = 1 + 2z + -1z2

Combine like terms: z2 + -1z2 = 0
7i + -1iz + 0 = 1 + 2z + -1z2
7i + -1iz = 1 + 2z + -1z2

Reorder the terms:
-1 + 7i + -1iz + -2z + z2 = 1 + 2z + -1z2 + -1 + -2z + z2

Reorder the terms:
-1 + 7i + -1iz + -2z + z2 = 1 + -1 + 2z + -2z + -1z2 + z2

Combine like terms: 1 + -1 = 0
-1 + 7i + -1iz + -2z + z2 = 0 + 2z + -2z + -1z2 + z2
-1 + 7i + -1iz + -2z + z2 = 2z + -2z + -1z2 + z2

Combine like terms: 2z + -2z = 0
-1 + 7i + -1iz + -2z + z2 = 0 + -1z2 + z2
-1 + 7i + -1iz + -2z + z2 = -1z2 + z2

Combine like terms: -1z2 + z2 = 0
-1 + 7i + -1iz + -2z + z2 = 0

The solution to this equation could not be determined.

See similar equations:

| -5x+2(-5x-5)=125 | | 2a+14a=20a-5a | | k/9=/18 | | 3-21=3x-9-2x | | -x+70=-86+5x | | 4(3x+2)-18= | | 6(z+2)-(6+4z)=z | | 3(x-3)=4(x+2) | | (4+4)(x+2)=(2+2) | | -5x=2x | | x^2-12x=8064 | | 8(5k-3)=-264 | | x^2-12x=5440 | | 9(y+5)=8y-6 | | 125*.38= | | -2x+2(-4x-3)=74 | | 4(y-8)=9+5y | | 28-6(2x+4)= | | 3(x+2)=4(x+2) | | 2x-1=63 | | z-(2+1i)z+(-1+7i)=0 | | 3(d-0.8)=4x+4 | | -34+3x=18+5x | | 19.3-4.507= | | 5x-31=2x+8 | | x+73=3x+9 | | 1-a^2=x^2-2ax+1 | | -6(2t+6)=-12 | | 3r=-18 | | x=7y-47 | | 0.14y+0.07(y+6000)=1260 | | 12-3(4x+2)=3x+4(x-8) |

Equations solver categories